2022
DOI: 10.1186/s12943-022-01631-8
|View full text |Cite
|
Sign up to set email alerts
|

A two-stage genome-wide association study to identify novel genetic loci associated with acute radiotherapy toxicity in nasopharyngeal carcinoma

Abstract: Background Genetic variants associated with acute side effects of radiotherapy in nasopharyngeal carcinoma (NPC) remain largely unknown. Methods We performed a two-stage genome-wide association analysis including a total of 1084 patients, where 319 individuals in the discovery stage were genotyped for 688,783 SNPs using whole genome-wide screening microarray. Significant variants were then validated in an independent cohort of 765 patients using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…39 Therefore, the response of normal tissues after radiotherapy can vary significantly among patients receiving similar treatment. Wang et al 8 found five single nucleotide polymorphisms are risk loci for skin toxicity and dysphagia in patients with NPC receiving radiotherapy. A recent study suggests that genetic susceptibility gene CEP128 affects the occurrence of RTLI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Therefore, the response of normal tissues after radiotherapy can vary significantly among patients receiving similar treatment. Wang et al 8 found five single nucleotide polymorphisms are risk loci for skin toxicity and dysphagia in patients with NPC receiving radiotherapy. A recent study suggests that genetic susceptibility gene CEP128 affects the occurrence of RTLI.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] However, despite similar clinical factors, there still exists interindividual variability, implying the existence of other crucial yet undiscovered factors that necessitate consideration. 8 It was reported that each patient's temporal lobe exhibits unique genetic susceptibility to radiation exposure and the genetic susceptibility gene CEP128 involved in RTLI development. 9 Additionally, He et al performed a genome-wide association study and developed a polygenic risk score for RTLI.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] Previously, we also performed a GWAS study of multiple acute radiotherapy toxicities in 1084 patients with nasopharyngeal carcinoma. Rs6711678, rs4848597, rs4848598 and rs2091255 on chromosome 2q14.2 and rs5845477 are novel risk loci for skin toxicity and dysphagia [ 20 ]. In this study, we provided the first GWAS study for radiotherapy response in NPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically relevant predictors of toxicity have also been found in many GWAS studies, e.g., SNPs predicting severe skin toxicity in patients with colorectal carcinoma treated with cetuximab ( Baas et al, 2018 ) or predicting dysphagia in patients with nasopharyngeal carcinoma treated with radiotherapy ( Wang et al, 2022 ) or predicting neurotoxicity and leukoencephalopathy in patients with lymphoblastic leukemia treated with methotrexate ( Bhojwani et al, 2014 ). Many other correlations between SNPs and toxicity can be found in the literature.…”
Section: Machine Learning In Cancer Researchmentioning
confidence: 99%